Influence of Fixation Mode and Superstructure Span upon Strain Development of Implant Fixed Partial Dentures - Matthias Karl, DMD,1 Manfred G. Wichmann, DMD,1 Werner Winter, Dr.-Ing.,2 (Journal of Prosthodontics, 2008)
Implant-borne fixed partial dentures (FPDs) should fit passively in order to avoid complications ranging from screw loosening to loss of osseointegration.